Baseline factors predicting a response to neoadjuvant chemotherapy with implications for non‐surgical management of triple‐negative breast cancer. Issue 5 (21st February 2018) - van la Parra, R. F. D.; Tadros, A. B.; Checka, C. M.; Rauch, G. M.; Lucci, A.; Smith, B. D.; Krishnamurthy, S.; Valero, V.; Yang, W. T.; Kuerer, H. M.
Abstract : Background: Patients with triple‐negative breast cancer (TNBC) and a pathological complete response (pCR) after neoadjuvant chemotherapy may be suitable for non‐surgical management. The goal of this study was to identify baseline clinicopathological variables that are associated with residual disease, and to evaluate the effect of neoadjuvant chemotherapy on both the invasive and ductal carcinoma in situ (DCIS) components in TNBC. Methods: Patients with TNBC treated with neoadjuvant chemotherapy followed by surgical resection were identified. Patients with a pCR were compared with those who had residual disease in the breast and/or lymph nodes. Clinicopathological variables were analysed to determine their association with residual disease. Results: Of the 328 patients, 36·9 per cent had no residual disease and 9·1 per cent had residual DCIS only. Patients with residual disease were more likely to have malignant microcalcifications ( P = 0·023) and DCIS on the initial core needle biopsy (CNB) ( P = 0·030). Variables independently associated with residual disease included: DCIS on CNB (odds ratio (OR) 2·46; P = 0·022), T2 disease (OR 2·40; P = 0·029), N1 status (OR 2·03; P = 0·030) and low Ki‐67 (OR 2·41; P = 0·083). Imaging after neoadjuvant chemotherapy had an accuracy of 71·7 (95 per cent c.i. 66·3 to 76·6) per cent and a negative predictive value of 76·9 (60·7 to 88·9) per cent for identifying residual disease in the breast and lymph nodes. Neoadjuvant chemotherapy did not eradicate the DCIS component in 55 per cent of patients. Conclusion: The presence of microcalcifications on imaging and DCIS on initial CNB are associated with residual disease after neoadjuvant chemotherapy in TNBC. These variables can aid in identifying patients with TNBC suitable for inclusion in trials evaluating non‐surgical management after neoadjuvant chemotherapy. Abstract : Ductal carcinoma in situ and microcalcification important